2019
DOI: 10.1111/his.13950
|View full text |Cite
|
Sign up to set email alerts
|

Management of radial scars/complex sclerosing lesions of the breast diagnosed on vacuum‐assisted large‐core biopsy: is surgery always necessary?

Abstract: Aims The diagnosis of radial scars/complex sclerosing lesions (RSs/CSLs) onpercutaneous biopsy carries a risk of histological underestimation. Consequently, surgical excision is often performed in order to exclude a possible associated malignancy. The aim of this study was to assess the rate of ‘upgrade to carcinoma’ upon subsequent surgical excision of RS/CSL cases diagnosed on vacuum‐assisted large‐core biopsy (VALCB). We also analysed the risk factors for upgrade in order to determine a subset of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
(100 reference statements)
1
7
0
Order By: Relevance
“…Another study demonstrating similar results is Kraft et al, where 50 of 50 patients undergoing active surveillance instead of excision did not progress on follow-up imaging (35). This is a larger cohort than in previous studies followed with imaging alone rather than surgical excision (23,33,34,38). For example, in Martaindale et al, 13 lesions were followed successfully for a median of 18 months with benign findings (33).…”
Section: Discussionsupporting
confidence: 55%
“…Another study demonstrating similar results is Kraft et al, where 50 of 50 patients undergoing active surveillance instead of excision did not progress on follow-up imaging (35). This is a larger cohort than in previous studies followed with imaging alone rather than surgical excision (23,33,34,38). For example, in Martaindale et al, 13 lesions were followed successfully for a median of 18 months with benign findings (33).…”
Section: Discussionsupporting
confidence: 55%
“…These may be the plausible reasons why SA could mimic invasive carcinoma on clinical and imaging presentation. Although research has reported that SA may convey an approximate doubling of breast cancer risk as a single feature, the presence of sclerosing adenosis alone in a core biopsy does not require surgical excision ( 29 , 30 ). Close clinical follow-up or routine imaging is recommended ( 1 , 7 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that imaging surveillance could be a reasonable option for RS without atypia assessed by 8-11G VAB. Likewise, Bacci et al [ 60 ] found that VAB with a large core is reliable to exclude malignancy and allows avoiding surgical excision when there is no discordance between radiological and histological findings, and no associated atypia on biopsy. Eghtedari et al [ 61 ] observed that in a group of 54 patients with a CNB histological result of RS without atypia, no case developed malignancy during the 2 years of follow-up (95% confidence interval 0–7%).…”
Section: Managementmentioning
confidence: 99%